Managing people in networked organisations - Grimshaw, Damian (Henry Stewart Talks, 2011)
Inter-organisational forms and multiple employers, Implications for HRM, Risk sharing and shared learning, Network characteristics (trust, dominance, modularity), Alignment, consistency and integration, Worker identity and engagement, Developing individual and organisational capabilities, Managing staff transfer in networks, Health and social care partnerships, IT outsourcing contracts, Public private partnerships